Stage-based model of population dynamics and harvest of Broad-snouted caiman (Caiman latirostris) under different management scenarios - V. Viotto, Evangelina; L. Navarro, Joaquín; S. Simoncini, Melina; Piña, Carlos (Ethnobiology and Conservation, 2023)
We created a matrix model structured by stages (divided into 5 stages) to evaluate the population dynamics of Caiman latirostris and the population behavior at different management intensities through ranching and hunting of adult individuals. We generated 5000 matrices by sampling the mean and variance values of survivals (pi) and hatching for each stage. For each matrix, we obtained the growth rate λ and performed elasticity analyses. Modifying the mean matrix obtained from the previous analysis, we evaluated different scenarios of ranching, reintroduction, and hunting of adult females of the last two stages (E) raised here (class III animals, > 60 cm snout-vent length, divided into two: E4 and E5). We obtained a mean λ of 1.035 (range 0.88 − 1.12), and 11.9% of the simulations had λ < 1. The vital rate with the highest elasticity and variance was that of the adult females of the last stage. Natural populations can tolerate a maximum of 5% adult female hunting, and ranching can extract 55% of nests from the wild without reintroduction or 80% of nest harvest, returning to the wild at least 3% of hatched animals in the ranching programs. Our model showed that hunting and ranching with reintroduction are feasible strategies to be applied without threatening natural populations. Increasing reintroduction makes it possible to extract more adult individuals and maintain the species’ populations at sustainable levels.